Efficacy of Acupoints Dual-Frequency Low-Level Laser Therapy on Knee Osteoarthritis. (24th September 2020) - Liao, Fang-Yin; Lin, Chien-Lin; Lo, Sui-Foon; Chang, Chun-Ching; Liao, Wen-Yen; Chou, Li-Wei
Abstract : Background . Knee osteoarthritis (OA) presented with knee pain and limitation of mobility is common, and it may become a chronic problem resulting in major loss of function, with related impaired activity of daily living. Current traditional therapy for knee OA includes pharmacological treatment and physiotherapy, but the efficacies are limited. An alternative noninvasive treatment low-level laser therapy (LLLT) applied to acupoints is still contradictory and the efficacy needs to be assessed. Methods and Materials . We conduct the randomized double-blind control study to investigate the efficacy of a dual-frequency LLLT (combines red light (780 nm) and near-infrared light (830 nm)) in patients suffering knee OA. Participates were randomly assigned into active laser therapy (ALT) and placebo laser therapy (PLT) groups. Subjects in the ALT group were separately treated by laser apparatus at the three acupoints (SP9, SP10, and EX-LE2) on their knee joints under continuous radiation for 15 min at the maximum intensity, three times per week for four weeks. The PLT group used laser apparatus of the same model according to similar procedures without laser light emission. Outcome Measurements including visual analog scale (VAS), pain pressure threshold (PPT), and Lequesne index were used. Results . A total of 30 subjects with two-sided knee OA in both groups completed the experiment. Statistically significant decreases were observed in the Lequesne index (5.27 ± 3.26 vs. 10.83 ± 3.83), conscious VAS 4 weeks after treatment (moving: 2.87 ± 1.13 vs. 5.67 ± 1.72; resting: 0.33 ± 0.62 vs. 2.67 ± 1.29), and the increase was noted in PPT (21.23 ± 1.82 kg vs. 13.02 ± 1.46 kg) in the ALT group compared with the PLT group. Conclusion . It appears that the knee OA pain and disability can be decreased after a dual-frequency LLLT applied to acupoints (SP9, SP10, and EX-LE2). The clinical efficacy of LLLT is highly related to the therapeutic settings of the laser apparatus; hence, more clinical trials with diffident parameter settings are needed to be further clarified.